Evaluating the Effectiveness of a Continuous Client Feedback System for Parolees Referred to Treatment: Benchmarking Treatment Outcomes - Grossl, Alyssa B. (2016)
Objective: The purpose of the present study was to evaluate the effectiveness of a group substance abuse program that incorporated continuous client feedback into treatment for parolees who had been referred to attend by the criminal justice system. Method: The pre-post treatment outcomes, as measured by the Outcome Rating Scale (ORS; Miller & Duncan, 2000), of 1,112 diverse parolees participating in treatment from October 2014 to January 2015 were analyzed. The most up-to-date benchmarking methodology was utilized to compare treatment outcomes observed in the naturalistic setting with those observed in rigorous randomized controlled trials evaluating the Partners for Change Outcome Management System (Duncan, 2012, 2014; Duncan & Sparks, 2010). Two sets of benchmarks were constructed for comparison purposes: one each for the feedback and treatment as usual conditions for two studies of PCOMS in a group setting and one each for the feedback and treatment as usual conditions for all six PCOMS studies. Results: Compared to the feedback condition benchmarks, the average treatment effect size estimate of psychotherapy for the present sample (d = 0.59) was not found to be clinically equivalent to the average effect size estimate from the two PCOMS group studies or to the effect size estimate constructed from all six PCOMS studies. In regards to treatment as usual, the effect size estimate from the present sample was found to be clinically superior to treatment as usual from all six PCOMS studies, including the two group randomized controlled trials. Conclusions: Despite the documented success in treatment outcomes regarding the use of continuous client feedback with voluntary clients, results suggest more modest effects with individuals referred to treatment. Although not found to be equivalent with the feedback conditions from randomized controlled trials, the use of client feedback with the present sample resulted in outcomes superior to those of treatment as usual in the six PCOMS studies. Particular characteristics of offender populations that can impact psychotherapy, and potentially treatment outcomes, are discussed